Relationship of nutritional completeness with events of stunting in children age 1- 2 years - Renaldi Gusela Wilian Nanda; Supriyadi (UM Purwokerto Press, 2020)
The problem of stunting is one of the nutritional problems that the world face, especially in poor and developing countries. Stunting is a chroniac malnutrition in the period of growth and development since early life. Nutrition is an important element in the fulfilment of nutritional needs because it serves to produce energy, build and maintain tissues, and regulate life processes in the body. In addition, nutrition is related to brain development, learning ability and work productivity. Stunting or short is a condition of failure to thrive in infants (0-11 months) and toddlers (12-59 months) as a result of chronic malnutrition, especially in the first 1,000 days of life so that the child is too short for their age. The objective is to determine the relation between the completeness of nutritional stats and the incidence of stunting in children aged of 1-2 years in the working area of Community Health Center I Kembaran. This type of research was quantitative using a descriptive correlation design with a cross sectional approach. The population in this study were children under 2 years who met the criteria. The sampling technique used was simple random sampling, namely 86 respondents were included. The analysis used was the chi square statistical test. Statistics in this study consisted of frequency of completeness of nutritional status with the occurrence of stunting in children aged 1-2 years. From the results of data processing, it was found that there was a relationship between the completeness of nutritional status with the incidence of stunting in children aged 1-2 years in the working area of Community Health Center I Kembaran with a p-value of 0,000 <0.005. There was a relationship between the completeness of nutritional status with the incidence of stunting in children aged 1-2 years in the working area of Community Health Center I Kembaran.